SYNTHESIS OF NITROGEN CERAMIC POWDERS BY CARBOTHERMAL REDUCTION AND NITRIDATION .1. SILICON-NITRIDE - CHO, YW; CHARLES, JA (INST MATERIALS, 1991)
Silicon nitride powders of high alpha-content were prepared from mixtures of very fine amorphous silica and carbon powders in flowing nitrogen at 1400-1500-degrees-C. The higher the reaction temperature within this range the lower the yield of silicon nitride in spite of a higher rate of SiO generation. The overall reaction rate increased with increasing nitrogen flowrate. An increase of carbon content of the starting mixtures increased the reaction rate by increasing the rate of SiO formation as well as the rate of Si3N4 nucleation. It is thought that the effect of the carbon particle size on the reaction rate is more significant than that of the specific surface area. The amount of silicon carbide formed and the alpha/beta-ratio in the reaction products were strongly affected by a change of the source of carbon used in the starting mixtures.
Keywords: CARBIDE WHISKERS; STABILITY; GROWTH; SI3N4